Influence of limestone dust and natural pozzolan on engineering properties of self-compacting repair mortars - Amar Benyahia; Said Choucha; Mohamed Ghrici; Ahmed Omran (Fracture and Structural Integrity)
The main goal of this work is the formulation of a self-compacting repair mortars (SCRMs) containing limestone dust (LD) and natural pozzolan (NP). For this purpose, a control mortar (SCRM-0) and two different mortars types, one with 10% LD (SCRM-10LD) and the other with 20% NP (SCRM-20NP) as cement replacements were prepared and tested according to EN 1504-3. The results of the experimental study showed that the produced repair materials fulfilled the performances requirements for structural repair products, class R4. In addition, the bond strength between the SCRMs and existing substrate concrete (SUBC), as assessed in this work by slant shear test on composite samples, showed that all tested samples have good bond strength at 28-days and the fractures were only occurred in the SUBC, which means that the substrate is the weakest link in the repair system